Measuring Radiological Parameters in Some Samples of Local and Imported Paints Buildingsin Najaf, Iraq - Allawi Hamead Alasadi (Journal of Kufa-Physics, 2018)
Exposure of the natural radioactivity available in soil and construction materials around the world occupies great concern because of the health risks associated with it. In this work, samples were collected from various markets in Najaf city, Iraq .The measurements of the paints samples have been carried out using gamma ray spectroscopy NaI(Tl) with that (“3×3”). The average value of specific activities were for238U, 232Th and 40K in different types of paints and dyes were 44.19±4.73Bq/Kg, 30.17±3.64 Bq/Kg and 478.84±10.34 Bq/Kg respectively. It is show that, the average value in samples under study were higher than the corresponding global values documented in (UNSCEAR2000) publications. All radiological parameters (Activity of Radium equivalentRaeq and out annual effective dose AEDout)were lower than the permissible limits except absorbed dose rate were higher than worldwide average (UNSCEAR, 2000).